Carbon Nanotubes: Current Perspectives on Diverse Applications in Targeted Drug Delivery and Therapies - Mohamed Rahamathulla (MDPI AG, 2021)
Current discoveries as well as research findings on various types of carbon nanostructures have inspired research into their utilization in a number of fields. These carbon nanostructures offer uses in pharmacy, medicine and different therapies. One such unique carbon nanostructure includes carbon nanotubes (CNTs), which are one-dimensional allotropes of carbon nanostructure that can have a length-to-diameter ratio greater than 1,000,000. After their discovery, CNTs have drawn extensive research attention due to their excellent material properties. Their physical, chemical and electronic properties are excellent and their composites provide great possibilities for enormous nanometer applications. The current study provides a systematic review based on prior literature review and data gathered from various sources. The various research studies from many research labs and organizations were systematically retrieved, collected, compiled and written. The entire collection and compilation of this review concluded the use of CNT approaches and their efficacy and safety for the treatment of various diseases such as brain tumors or cancer via nanotechnology-based drug delivery, phototherapy, gene therapy, antiviral therapy, antifungal therapy, antibacterial therapy and other biomedical applications. The current review covers diverse applications of CNTs in designing a range of targeted drug delivery systems and application for various therapies. It concludes with a discussion on how CNTs based medicines can expand in the future.